Toxicity assessment of advanced biological wastewater treatment plant effluent by integrated biomarker response in zebra mussels (Dreissena polymorpha) - Serdar Osman; Ketenalp Zozan; Yildirim Nuran Cikcikoglu (Oceanological and Hydrobiological Studies)
In this study, zebra mussels (Dreissena polymorpha) were exposed to advanced biological wastewater treatment plant effluent (ABWTPE) for 96 h. At the end of the 96th hour, antioxidant parameters such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX), glutathione S-transferase (GST), malondialdehyde (MDA) and glutathione (GSH) were examined. The objective of the study was to identify biomarkers that are useful for assessing the potential toxic effects of ABWTPE in freshwater environments. We observed an increase in GPX, SOD activity and MDA levels, and a decrease in CAT, GST activity and GSH levels. The results obtained in our study showed that the measured biochemical parameters (GSH, MDA, SOD, CAT, GPX and GST) are useful biomarkers in determining the possible toxicity of ABWTPE in aquatic environments.